Energy Efficiency Policies in Turkey: The Case for Standards and Labels - Kama, Ozge; Kaplan, Zeynep (International Journal of Energy Economics and Policy, 2013)
Recently, Turkey is attempting to improve its energy efficiency policies. As the demand of energy is increasing in Turkey, improving energy efficiency can be considered as an efficient way to achieve its sustainable development goals. In this respect, government policies and program strategies must be designed to overcome persistent market barriers against energy efficient household appliances. Label and standard programs can be used as a strategy to improve energy efficient products. With this issue in mind, the aim of this paper is to provide a broad overview of appliance efficiency standards and labeling programs in Turkey. The paper consists of five sections: After a brief introduction on the subject, the second section deals with the market transformation for energy efficient products. In the third section, legal issues related to energy efficiency will be discussed. Then in the next section, current situation and challenges related to labeling appliances will be analyzed and the paper concludes with a brief summary. Keywords: Electrical consumption; energy efficiency; market transformation; energy labelling JEL Classifications: Q01; Q43; Q48